Inflammatory Immune Cytokine TNF-α Modulates Ezrin Protein Activation via FAK/RhoA Signaling Pathway in PMVECs Hyperpermeability - Zhou, Qun; Jiang, Jianjun; Chen, Guanjun; Qian, Cheng; Sun, Gengyun (Frontiers in Pharmacology, 2021)
Background: One of the important pathogenesis of acute respiratory distress syndrome (ARDS) is the dysfunction of pulmonary microvascular endothelial barrier induced by a hyper-inflammatory immune response. However, the potential mechanisms of such an imbalance in pulmonary microvascular endothelial cells (PMVECs) are not yet understood. Purpose: Explore the molecular mechanism of endothelial barrier dysfunction induced by inflammatory immune cytokines in ARDS, and find a therapeutic target for this syndrome. Methods: Rat PMVECs were cultured to form a monolayer. Immunofluorescence, flow cytometry and western blotting were selected to detect the distribution and the expression level of phosphorylated Ezrin protein and Ezrin protein. Transendothelial electrical resistance (TER) and transendothelial fluxes of fluorescein isothiocyanate (FITC)-labeled bovine serum albumin (BSA) were utilized to measure the permeability of the cell monolayer. Ezrin short hairpin RNA (shRNA) and Ezrin 567-site threonine mutant (EzrinT567A) were used to examine the role of Ezrin protein and phosphorylated Ezrin protein in endothelial response induced by tumor necrosis factor-alpha (TNF-α), respectively. The function of focal adhesion kinase (FAK) and Ras homolog gene family, member A (RhoA) signalling pathways were estimated by inhibitors and RhoA/FAK shRNA in TNF-α-stimulated rat PMVECs. The activation of FAK and RhoA was assessed by western blotting or pulldown assay plus western blotting. Results: The TER was decreased after TNF-α treatment, while the Ezrin protein phosphorylation was increased in a time- and dose-dependent manner. The phosphorylated Ezrin protein was localized primarily at the cell periphery, resulting in filamentous actin (F-actin) rearrangement, followed by a significant decrease in TER and increase in fluxes of FITC-BSA. Moreover, FAK and RhoA signalling pathways were required in the phosphorylation of Ezrin protein, and the former positively regulated the latter. Conclusion: The phosphorylated Ezrin protein was induced by TNF-α via FAK/RhoA signalling pathway, leading to endothelial hyperpermeability in PMVECs.